An assessment of a performance-based management agreement initiative in Ghana's health service - Edmund Wedam Kanmiki; Ben Owusu Smith Bempah; John Koku Awoonor-Williams; Ayaga A. Bawah; Selassi Amah d'Almeida; Kassem M. Kassak (BMC, 2018)
Abstract Background As part of its efforts to improve efficiency, accountability and overall performance, the Ghana Health Service (GHS) introduced annual Performance-based Management Agreements (PMAs) in the year 2013. However, no assessment of this initiative has since been made in order to inform policy and practice. This paper provides an assessment of this policy initiative from the perspective of managers at various levels of service implementation. Methods Mixed methods were employed. Questionnaires were administered to managers through an online survey (using Google forms). Descriptive and inferential statistical methods were used to analyze and present quantitative results while qualitative data was analyzed via thematic analysis. Results The content and objectives of the PMAs were observed to be comprehensive and directed at ensuring high performance of directorates. Targets of PMAs were found to be aligned with overall health sector objectives and priorities. The directors felt PMAs were useful for delegating task to subordinates. PMAs were also found to increase commitment and contributed to improving teamwork and prudent use of resources. However, PMAs were found to lack clear implementation strategies and were not backed by incentives and sanctions. Also, budgetary allocations did not reflect demands of PMAs. Furthermore, directors at lower levels were not adequately consulted in setting PMAs targets as such district specific challenges and priorities are not usually factored into the process. Insufficient training of staff and lack of requisite staff were key challenges confronting the implementation of PMAs in most directorates. Weak monitoring and evaluation was also observed to significantly affect the success of PMAs. Conclusion There is the need to address the weaknesses and improve on the existing strengths identified by this assessment in order to enhance the effectiveness of PMAs utilization in the Ghana health service.